ANALISIS METAFORA DALAM LIRIK LAGU FIREFLIES - varia virdania virdaus (MOTORIC, 2021)
The purpose of this study is to find out the types of metaphors and their meanings in the lyrics of the song Fireflies sung by Owl City. The research method used descriptive (qualitative). Documentation technique was applied to perform data analysis, in this case the text of the fireflies song lyrics as the data source used. The results showed that there were three types of metaphors in the lyrics of the song, including structural metaphors, orientational metaphors, and ontological metaphors. The meaning of the figurative meaning of the fireflies song lyrics was to do everything you like, appreciated the time and the little things around you, because they couldn't be repeated, and things didn't always have to be what we want